Politeness in Language of Female Students of the Al-Ishlahiyah Salafiyah Islamic Boarding School for Girls in Malang City - Muhammad Ayyinna Yusron El Farouq (PT. Anagata Sembagi Education, 2025)
The purpose of this study is to describe the linguistic disturbance in the surroundings of the Salafist guest house of Al-Islahiyah's daughter of the Poor City. The author's research is included in qualitative descriptive research. Data collection techniques are performed using observation and interview methods. Data analysis uses qualitative descriptive analysis techniques, i.e. written or oral data of people and behavior observed in formal and informal situations in the training environment. The results of the research showed that the santri had the ability to speak the shantun language that could bring goodness and goodness to the environment of the hostel. It can be seen in the phenomenon of the speech of the chancellor of the Salafist house of the daughter of Al-Islahiyah. The results of this study show that there are several maxims of humility used by women in interaction, namely (1) the maxim of wisdom, (2) the maximum of charity, (3) the maximum acceptance, (4) the maximum humility, (5) the maximum agreement, and (6) the maximum sympathy.